Currículo e emancipação: redimensionamento de uma escola instituída em um contexto advindo do processo de desfavelização - Felício, Helena Maria dos Santos (2008)
This study analyzes the construction of a curriculum with the potential for emancipation in educational quotidian experience. It is based on the analysis of educative practices developed by educators in the initial years of primary education who work in an educational context that attends students in a community that is in the process of being taken out of a shantytown in the municipality of São José dos Campos (SP). The educational context investigated comprises a partnership between a regular public school and a formal educational institution in the community, in order to develop the educational process amongst the children and teenagers in the integral education provided. The investigation was developed from a qualitative standpoint, including bibliographical research, participatory observation, documental analysis and interviews with the educators from the two institutions comprising the context analyzed. We observed that the need to consider the social context the institutions are installed in led to the proposal for curricular redesign in order to construct and conceive of an extended curriculum that integrates in itself with the formal and informal dimension of education, as articulating dimensions. Based on this analysis it was possible to check the possibility of building pedagogical practices with the potential for emancipation to the extent that the institutions and educators are capable of deconstructing their conceptions of what its is to teach and learn, generally marked by traces of transmission, to develop practices based on the principle of construction, interaction, exchange, respect, and creativity with the students themselves. We conclude in this study that a curriculum with the potential for emancipation could be built when the educational institutions are encouraged to take a critical look at their quotidian experience, being able to propose action that is the fruit of interaction with the community and culture they are in